Local delivery of thyroid hormone enhances oligodendrogenesis and myelination after spinal cord injury. (30th March 2017) - Shultz, Robert B; Wang, Zhicheng; Nong, Jia; Zhang, Zhiling; Zhong, Yinghui
Abstract: Objective . Traumatic spinal cord injury (SCI) causes apoptosis of myelin-forming oligodendrocytes (OLs) and demyelination of surviving axons, resulting in conduction failure. Remyelination of surviving denuded axons provides a promising therapeutic target for spinal cord repair. While cell transplantation has demonstrated efficacy in promoting remyelination and functional recovery, the lack of ideal cell sources presents a major obstacle to clinical application. The adult spinal cord contains oligodendrocyte precursor cells and multipotent neural stem/progenitor cells that have the capacity to differentiate into mature, myelinating OLs. However, endogenous oligodendrogenesis and remyelination processes are limited by the upregulation of remyelination-inhibitory molecules in the post-injury microenvironment. Multiple growth factors/molecules have been shown to promote OL differentiation and myelination. Approach . In this study we screened these therapeutics and found that 3, 3′, 5-triiodothyronine (T3) is the most effective in promoting oligodendrogenesis and OL maturation in vitro . However, systemic administration of T3 to achieve therapeutic doses in the injured spinal cord is likely to induce hyperthyroidism, resulting in serious side effects. Main results . In this study we developed a novel hydrogel-based drug delivery system for local delivery of T3 to the injury site without eliciting systemic toxicity. Significance . Using a clinically relevant cervical contusion injury model, we demonstrate that local delivery of T3 at doses comparable to safe human doses promoted new mature OL formation and myelination after SCI.